Teaching program for beginners in alpine skiing competition - Kondo, Y.; Takeda, T.; Shindo, S. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The purpose of this study is to present a teaching program for beginners in alpine skiing that makes learners feel enjoyment, and assists learners in mastering the technique and the tactics of the sport.